ROA STRATEGY FOR FIRM SIZE COMPANIES IN INVESTMENT SUB-SECTORS LISTED ON THE IDX - Atqi, Muhammad Fatkhul; Setiawati, Ira; Puspitasari, Ratih Hesti Utami (Universitas PGRI Semarang, 2024)
AbstractThis study aims to find out and analyze the influence of Debt to Equity Ratio, Working Capital Turnover and Firm Size on Return on Assets in investment sub-sector companies listed on the IDX. The profitability ratio is a ratio used to measure a company's ability to generate profits from its activities. The collection technique of this research uses the method of documentation and literature study. are quantitative in nature sourced from secondary data. in the form of numbers. The number of investment sub-sector companies sampled was 13 companies, so the total sample used was 65 financial statements. Financial statements are published by companies listed on the IDX from 2018 to 2022 through its official website www.idx.co.id. The method used is multiple linear regression analysis with Eviews Software 13. The results showed that Delbt To Equity Ratio (DElR) had a positive and significant effect on Relative Turn on Assets (ROA), Working Capital Tulrnover (WCT) had no positive and significant effect on ROA, and Firm Size had no significant and negative effect on ROA. The variables Debt to Equlity Ratio, Working Capital Turnover, and Firm Size together (simultaneously) affect ROA, and only contribute 14.9% to the ROA of investment sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period.Â Â